Perbandingan Efektivitas Sistem Pembelajaran Luring dan Daring Menggunakan Metode Use case dan Sequence Diagram - Ricky Rohmanto; Topan Setiawan (Masoem University, 2022)
Ma’soem University is a formal educational institution that has implemented an offline and online learning system. This study aims to assess the effectiveness of the two learning systems globally and determine which learning system is more suitable to be applied to students and propose improvements to the learning system that is considered less effective. The research method used is a survey in which respondents are asked eight questions related to both learning systems, the technique of analysis and data processing is done by using descriptive statistics, meanwhile the proposed system improvement is visualized using use case diagrams and sequence diagrams. Based on the research results, the respondents stated that the offline learning system was considered more effective with a percentage of 64,99%, compared to online learning system with a percentage of 31,52%, so it is proposed to improve the online learning system by building an e-learning system.